The Impact of Transient Ischemic Attack (TIA) on Brain and Behavior - Simmatis, Leif E. R.; Scott, Stephen H.; Jin, Albert Y. (Frontiers in Behavioral Neuroscience, 2019)
Transient ischemic attack (TIA) was originally defined as self-resolving focal cerebral ischemia with symptoms lasting <24 hours. The newer definition also added the limitation that there should be no evidence of acute brain tissue infarction, to recognize that acute injury to the brain can result from ischemia of <24-hour duration. However, several recent findings suggest that having a TIA correlates with deficits that can persist far beyond the resolution of clinical symptoms, even in the absence of imaging evidence of ischemic tissue injury. These deficits may be the result of subtle perturbations to brain structure and/or function that are not easily appreciated using the standard clinical and imaging tools that are currently employed in practice. Here, we will discuss evidence that suggests that TIA may lead to lasting changes to the structure and function of the brain.